2013
DOI: 10.1042/bj20130123
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleases as a host-defence family: evidence of evolutionarily conserved antimicrobial activity at the N-terminus

Abstract: Vertebrate secreted RNases (ribonucleases) are small proteins that play important roles in RNA metabolism, angiogenesis or host defence. In the present study we describe the antimicrobial properties of the N-terminal domain of the hcRNases (human canonical RNases) and show that their antimicrobial activity is well conserved among their lineage. Furthermore, all domains display a similar antimicrobial mechanism, characterized by bacteria agglutination followed by membrane permeabilization. The results of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 44 publications
9
53
0
Order By: Relevance
“…No activity was detected under the same assayed conditions for pure neutral vesicles (data not shown), as previously observed for RNase 3 (41). The data also confirmed that the cell agglutination was specific for the tested Gram-negative species, as previously reported for the other assayed RNase peptides (17,33). Most importantly, no detectable hemolysis was found at concentrations up to 25 M, and 50% lysis was achieved at 217 Ϯ 42.17 M for the RNase 3 protein and 178,33 Ϯ 81.72 M for the RN3(5-17P22-36) peptide.…”
Section: Antimicrobial Peptide Designsupporting
confidence: 79%
See 2 more Smart Citations
“…No activity was detected under the same assayed conditions for pure neutral vesicles (data not shown), as previously observed for RNase 3 (41). The data also confirmed that the cell agglutination was specific for the tested Gram-negative species, as previously reported for the other assayed RNase peptides (17,33). Most importantly, no detectable hemolysis was found at concentrations up to 25 M, and 50% lysis was achieved at 217 Ϯ 42.17 M for the RNase 3 protein and 178,33 Ϯ 81.72 M for the RN3(5-17P22-36) peptide.…”
Section: Antimicrobial Peptide Designsupporting
confidence: 79%
“…The antimicrobial activity of the secreted human RNases is mainly located at the N-terminal region (17). Accordingly, the RNase antimicrobial scaffold was engineered to produce new antimicrobial peptides (23,33,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Anantharaman et al (127) showed that a combination of four designed peptides, which had poor to moderate antimicrobial activity, with rifampicin or kanamycin enhanced their potencies against E. coli 4-to 34-fold, respectively. Synergistic effects were reported for the lactoferrin-derived peptide hLF (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and fluconazole against C. albicans. It was also observed that lactoferrin or hLF(1-11) added in subinhibitory concentrations to antifungal agents such as clotrimazole, ketoconazole, and intraconazole reduced the minimum inhibitory concentration of these agents against Candida species (108,128,129).…”
Section: Potential Applications Of Antimicrobial Peptidesmentioning
confidence: 93%
“…In addition, small proteins, e.g. RNase A family members, also exhibit antimicrobial activity, and their involvement in anti-pathogen defense has been well documented (7). Usually, a set of defense peptides differing in biochemical properties and mechanism of antimicrobial action is synthesized by a given organism.…”
Section: Introductionmentioning
confidence: 98%